Ontogenetic changes in the shoot primary vasculature of Anagallis arvensis L. - Dorota Kwiatkowska (Acta Societatis Botanicorum Poloniae, 2014)
Ontogenetic changes in the primary vasculature of Anagallis shoots are strictly related to phyllotaxis. During the ontogeny of Anagallis, whorled and spiral phyllotactic patterns appear alternately in a regular sequence. The initial decussate phyllotaxis is transformed into the spiral Fibonacci, and then further into trimerous pattern. This in turn may change into the spiral Lucas phyllotaxis. Sporadically the immediate transition from the decussate to trimerous phyllotaxis takes place. The vascular system in Anagallis is always closed, despite that both whorled and spiral phyllotaxes are present. Also the number of vascular traces diverging to the leaf is constant. In the course of a single phyllotactic transition, there is an increase in the number of vascular sympodia and in the number of leaf traces present in the vascular cylinder. Usually only one single sympodium and one or two traces are added to the system. The immediate addition of two sympodia occurs only during infrequent transition from the decussate to trimerous pattern. The increase in the number of sympodia is most often simultaneous with the phyllotactic transition, however, when the trimerous pattern is transformed into the spiral Lucas, the increase is delayed, sometimes for as much as ten plastochrons. In shoots with changing phyllotaxis, a sector within the vascular cylinder can be distinguished, in which the leaf traces are arranged as if the previous phyllotactic pattern continued, whereas rearrangement of traces takes place at the same level but in the complementary sector. This is in agreement with the concept of discontinuous circumferential changes in the shoot apex being responsible for qualitative transformations of phyllotaxis.